CULTURE–INCLUSIVE TOILET DESIGN FOR YPAB BLIND SCHOOL IN SURABAYA - Gunawan, TANUWIDJAJA (DIMENSI (Journal of Architecture and Built Environment), 2014)
Toileting culture affects the toileting design. Adaptive - inclusive toilet design strategy was needed to respond the local unique toileting culture of Surabaya people. Based on toileting culture and five Inclusive design principles directed by Tanuwidjaja, the inclusive toilet was produced. The project involved four steps such as: literature review, interview and photo documents, participative design workshops and design development. Therefore, a final design was produced and found acceptable for Surabaya people.